2011
DOI: 10.4161/psb.6.10.16876
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine promotes the emergence and elongation of lateral roots ofRaphanus sativus

Abstract: radish (Raphanus sativus L.) was grown on four layers of paper towel moistened with distilled water with and without acetylcholine (ach) for five days in the dark after sowing. ach at 1 nM promoted the growth (emergence and elongation) of lateral roots of radish plants, but had no effect on the stems and main roots. Moreover, ach enhanced the dry weight of roots [main (primary) + lateral roots]. Neostigmine, an inhibitor of acetylcholinesterase (ache) also promoted the emergence and elongation of lateral roots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
(41 reference statements)
0
15
0
Order By: Relevance
“…Moreover, serotonin, tryptophan-derived transmitter conserved in plants and animals, is structurally similar to auxin (Pelagio-Flores et al, 2011). In addition to serotonin, L-glutamate, and acetylcholine are also known to regulate root growth and root system architecture, the latter as a ligand of plant glutamate receptor-like channels (Sagane et al, 2005; Walch-Liu et al, 2006; Sugiyama and Tezuka, 2011; Price et al, 2012b; Forde et al, 2013; Vincill et al, 2013). During plant sexual reproduction, communication between the male gametophyte and the female pistil tissue has been shown to be mediated by the amino acid D-serine via GLRs; this is strongly reminiscent of neuronal synaptic communication in animals (Michard et al, 2011).…”
Section: Auxin and Neurotransmitters Control Root System Architecturementioning
confidence: 99%
“…Moreover, serotonin, tryptophan-derived transmitter conserved in plants and animals, is structurally similar to auxin (Pelagio-Flores et al, 2011). In addition to serotonin, L-glutamate, and acetylcholine are also known to regulate root growth and root system architecture, the latter as a ligand of plant glutamate receptor-like channels (Sagane et al, 2005; Walch-Liu et al, 2006; Sugiyama and Tezuka, 2011; Price et al, 2012b; Forde et al, 2013; Vincill et al, 2013). During plant sexual reproduction, communication between the male gametophyte and the female pistil tissue has been shown to be mediated by the amino acid D-serine via GLRs; this is strongly reminiscent of neuronal synaptic communication in animals (Michard et al, 2011).…”
Section: Auxin and Neurotransmitters Control Root System Architecturementioning
confidence: 99%
“…In this study, it was observed that the application of Ach in plants under osmotic stress -1 MPa (Table 1) promoted an elongation of the roots of seedlings. This phenomenon is dependent on the metabolic activity resultant in induction or inhibition of enzyme activity regulators in plant growth (Sugiyama and Tezuka 2011). Sugiyama and Tezuka (2011) carried out experiments with the application of Ach and observed the emergence and elongation of lateral roots in Vigna sesquipedalis (L.) Fruwirth, Avena sativa L. and Raphanus sativus (radish) grown in the dark.…”
Section: Discussionmentioning
confidence: 99%
“…According to Murch (2006), increased growth and cell wall thickness occur because Ach is synthesized in the stems, leaves and root nodes in response to stress. Sugiyama and Tezuka (2011) analyzed the application of Ach in radish seeds, obtaining as a result a small effect on the fresh weight of the roots, while approximately a doubling of dry weight was observed. Ach exhibits an ability to increase the translocation of carbohydrates, such as sugars and starch, from the cotyledons to the roots, providing a higher elongation of roots and also higher biomass accumulation (Sugiyama and Tezuka 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the effects of ACh on several growth and developmental phenomena in plants have been conducted (Tretyn and Kendrick 1991). Sugiyama and Tezuka (2011) revealed that the emergence and elongation of lateral roots of Raphanus sativus could be regulated by 1 nM ACh. Braga et al (2017) showed that the growth and dry matter accumulation were promoted by ACh under osmotic stress in soybean seedlings.…”
Section: Introductionmentioning
confidence: 99%